Synthesis and Characterization of Nano Ti-50%AI by Mechanical Alloying - Al-Dabbagh, Jinan B.; Razman, Mat Tahar; M., Ishak; Siti Aisyah, Harun
In this study, powder metallurgy process of TiAI nano alloys were performed via mechanical alloying (MA) of Ti-50%AI powder using planetary ball milling equipment.